Harnessing AI: Enhancing Academic Reading Skills in English for Academic Purposes - Hasyim, Fuad (English Education Study Program, 2025)
The study aims to explore how AI-based technologies can revolutionize traditional pedagogy by creating more engaging and personalized learning experiences. Specifically, the research analyzes applications such as Storm AI, Simplified AI, SciSpace, Sread, SciSummary, Google Translate, and Read & Write, focusing on their capabilities to enhance reading comprehension, vocabulary acquisition, and analytical skills. The data collection process involved systematically sourcing articles from reputable journal indexes that focus on the application of AI in educational contexts, particularly in enhancing academic reading practices. Utilizing descriptive analysis, the study synthesizes findings from these diverse studies to identify common themes, trends, and implications regarding the integration of AI technologies in academic reading. The findings demonstrate that AI tools can mitigate common challenges faced by business English learners, facilitate self-regulated learning, and be tailored to individual needs. However, the study also highlights ethical concerns, including potential biases and privacy issues. In conclusion, the article underscores the transformative potential of AI in academic reading and language education while emphasizing the need for responsible implementation to address ethical challenges and maximize its benefits for educators and learners.